2020
DOI: 10.1109/access.2020.2970921
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Wired and Wireless Virtual Reality Setups

Abstract: Virtual Reality (VR) through head-mounted displays (HMDs) can be delivered via multiple setups such as smartphones, standalone VR or VR Workstations. The VR Workstation setup delivers the best performance of them all; however, as a drawback up until recently, it required cables to power up the VR equipment. The introduction of wireless solutions for VR Workstations came to solve one of the disadvantages of this setup. However, the impact of the wireless solution versus the HMD cables was not yet properly inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
1
1
0
2
Order By: Relevance
“…a break in presence). Other studies have reported similar issues (see [ 48 , 49 ]). The presence ratings were high, indicating that both the environment and dog model were deemed to have high levels of realism and immersion.…”
Section: Discussionsupporting
confidence: 66%
“…a break in presence). Other studies have reported similar issues (see [ 48 , 49 ]). The presence ratings were high, indicating that both the environment and dog model were deemed to have high levels of realism and immersion.…”
Section: Discussionsupporting
confidence: 66%
“…One study Han et al (2017) compared a mobile HMD setup (Samsung Galaxy 7) to a dedicated HMD device (LG G5) in virtual outdoor environments. Another study Gonçalves et al (2020) compared wired and wireless VR setups. Participants navigated a virtual building interior using either a wireless HTC VIVE, a wired HTC Vive with the aid of a researcher managing the cable for them, or a wired HTC Vive on their own.…”
Section: Viewing Hardwarementioning
confidence: 99%
“…As diferenc ¸as mais perceptíveis do DPOC-VR, comparado à sua versão mobile, são a remoc ¸ão de itens coletáveis que obrigavam o jogador a pausar a corrida para responder a perguntas de conhecimentos médicos referentes a DPOC. O objetivo é evitar quebras de presenc ¸a, o que pode influenciar na experiência do jogo em VR [Gonc ¸alves et al 2020].…”
Section: Materiais E Métodosunclassified